Behavioral economic substitutability of e-cigarettes, tobacco cigarettes, and nicotine gum. (July 2017) - Johnson, Matthew W; Johnson, Patrick S; Rass, Olga; Pacek, Lauren R
The public health impact of e-cigarettes may depend on their substitutability for tobacco cigarettes. Dual users of e-cigarettes and tobacco cigarettes completed purchasing tasks in which they specified daily use levels under hypothetical conditions that varied the availability and price of e-cigarettes, tobacco cigarettes, and nicotine gum (for those with nicotine gum experience). When either e-cigarettes or tobacco cigarettes were the only available commodity, as price per puff increased, purchasing decreased, revealing similar reinforcement profiles. When available concurrently, as the price of tobacco puffs increased, purchasing of tobacco puffs decreased while purchasing of fixed-price e-cigarette puffs increased. Among those with nicotine gum experience, when the price of tobacco puffs was closest to the actual market value of tobacco puffs, e-cigarette availability decreased median tobacco puff purchases by 44% compared to when tobacco was available alone. In contrast, nicotine gum availability caused no decrease in tobacco puff purchases. E-cigarettes may serve as a behavioral economic substitute for tobacco cigarettes, and may be a superior substitute compared to nicotine gum in their ability to decrease tobacco use. Although important questions remain regarding the health impacts of e-cigarettes, these data are consistent with the possibility that e-cigarettes may serve as smoking cessation/reduction aids.